The use of dialogic strategy clusters for vocabulary learning by Chinese students in the UK. (July 2015) - Wang, Kai-Hui (Isobel)
Abstract: Large-scale questionnaire surveys tend to treat learners' vocabulary strategy use as relatively stable and removed from their context. More research is needed to explore learners' vocabulary strategy use within particular contexts. Using data collected from classroom observation, interviews and VOCABlog (including photovoice and diaries), the researcher investigated the strategic vocabulary learning process of two Chinese students who were on a pre-university course at two British universities from both cognitive and sociocultural perspectives. This paper provides a more holistic view of strategic vocabulary learning, and examines the dynamic, complex and contextually situated nature of learners' strategy use. The findings imply that in order to enhance their vocabulary learning, international students should seek opportunities to engage with target language speakers and pay particular attention to the contexts where they learn vocabulary. They also need make deliberate and continuous efforts to form dynamic strategy combinations through verbal interaction with more capable others.